Pemberian Probiotik EM-4 (Effective Mikroorganism 4) Untuk Menumbuhkan Klekap Sebagai Pakan Alami Guna Meningkatkan Pertumbuhan Dan Survival Rate Benih Ikan Bandeng (Chanos sp.) - Rifka Ayu Layyinah; Pungky Slamet Wisnu Kusuma; Dyah Hariani (Universitas PGRI Adi Buana Surabaya, 2025)
The study aimed to determine the effect of EM-4 probiotic administration on natural klekap feed with different doses on the growth and survival of milkfish (Chanos sp) seeds. The test fish of milkfish (Chanos sp) with a length of 2 cm and a weight of 2 grams came from a milkfish seed cultivation reservoir in Mengarih Village, Manyar District, Gresik Regency, randomly stocked into 12 ponds with a fish density of 30 fish/pond and tested for 30 days. This study used a Complete Random Design with 4 treatments and 3 replicates. The treatment given was the difference in the dose of probiotics added in klekap natural feed, which consisted of treatment without the addition of probiotics, treatment with the addition of probiotics as much as 15 ml/L, 25 ml/L, 35 ml/L. Data were analyzed using Variety Analysis (ANOVA) with a level of (P<0.05). Test parameters included absolute weight growth rate (LPBM), absolute length growth (PPM), and survival rate (SR). The results showed that the administration of EM-4 on different natural klekap feeds had a real effect (P<0.05) on LPBM, PPM, and SR. The best values were for LPBM (5.73±0.14 grams), PPM (10.33±0.04 mm). The average success rate (SR) during the experiment was approximately 88.75%. Keywords: Milkfish Seed (Chanos Sp), Survival, Klekap, Probiotic EM-4, Growth